Evaluating public compliance with wildlife conservation law in Wuhan, China - Sharaai, Amir Hamzah; Yujing, Zha; Wafa, Wafaurahman; Sining, Ma; Zhijian, He (Malaysian Institute of Planners, 2023)
As a result of the outbreak of COVID-19 in mainland China, the governments expedite the legislation of the Wildlife Protection Law (WPL) by proposing a comprehensive prohibition on wildlife eating and trading in the latest WPL due to the potential association between the outbreak and wildlife. However, the prohibition could affect the current social-economic system, leading to a void of legislation due to the disobedience of laws in society. Public readiness toward the law has a strong relationship with expected obedience to it. Therefore, the objectives of this study are to assess the two components of the readiness knowledge about the law and the readiness toward the actions potentially contradicting the latest WPL. Another objective is to collect participants' opinions and reasons on whether they think the latest WPL is difficult to enforce. By selecting the epicenter Wuhan as a study site, voluntary response sampling was used to distribute the questionnaire online. The data obtained from 410 respondents show that the citizens in Wuhan have average knowledge about the latest WPL but are unaware of the definition of wildlife. Based on the Mann-Whitney test, the study found no significance between gender and knowledge, but it exists in all other comparisons. Moreover, the significance only exists between readiness scale and age groups. The difficulty in enforcing the latest WPL underlines the problems in enforcement, awareness, demand, and society aspect, while on the opposite, respondents highlight the lesson from the pandemic and belief in the governments. In conclusion, citizens in Wuhan show a medium readiness toward the latest WPL, which is vital to design optimal legislation.